2023
DOI: 10.3389/fgene.2023.1158293
|View full text |Cite
|
Sign up to set email alerts
|

Association of the gut microbiota with coronary artery disease and myocardial infarction: A Mendelian randomization study

Abstract: Background: Previous studies have indicated that the gut microbiota (GM) is associated with coronary artery disease (CAD), but the causality of these associations remains unestablished due to confounding factors and reverse causality. We conducted Mendelian randomization study (MR) to determine the causal effect of the specific bacterial taxa on CAD/myocardial infarction (MI) and identify the mediating factors involved.Methods: Two-sample MR, multivariable MR (MVMR) and mediation analysis were performed. Inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…The gut microbiota is a complex and diverse community of microorganisms that inhabits the gastrointestinal tract and plays a crucial role in regulating metabolism, immunity, and inflammatory processes. Additionally, recent research has revealed that the bacteria in atherosclerotic plaques are analogous to those that colonize the gut[ 51 ]. One of the metabolites produced by the gut microbiota is trimethylamine-N-oxide (TMAO)[ 4 ], which is derived from dietary sources such as choline, betaine, and L-carnitine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gut microbiota is a complex and diverse community of microorganisms that inhabits the gastrointestinal tract and plays a crucial role in regulating metabolism, immunity, and inflammatory processes. Additionally, recent research has revealed that the bacteria in atherosclerotic plaques are analogous to those that colonize the gut[ 51 ]. One of the metabolites produced by the gut microbiota is trimethylamine-N-oxide (TMAO)[ 4 ], which is derived from dietary sources such as choline, betaine, and L-carnitine.…”
Section: Discussionmentioning
confidence: 99%
“…One of the metabolites produced by the gut microbiota is trimethylamine-N-oxide (TMAO)[ 4 ], which is derived from dietary sources such as choline, betaine, and L-carnitine. TMAO has been linked to the development and progression of CAD due to its pro-inflammatory effects and its inhibition of reverse cholesterol transport[ 51 ]. With their higher intake of red meat, Omnivores are significantly more susceptible to CVD than those who consume PBDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure adequate selection of IVs, SNPs with P values below the genome-wide significance threshold (1 × 10 -5 ) were chosen. According to previous research, [ 16 , 17 ] the LD parameter (r 2 ) for SNPs was set at 0.001, with a genetic distance of 10000 kb, to examine the independence of variables and LD effects. The PhenoScanner website was subsequently utilized in January 2024 to check for associations between IVs and potential confounders, such as smoking and alcohol consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, large-scale GWAS data on gut microbiota, blood metabolites, CAD, and cognitive impairment are publicly available, creating opportunities for us to investigate the causal associations between gut microbiota, blood metabolites, and the disease cluster of CAD combined with cognitive impairment through MR. Previously, some researchers have found causal links between specific gut microbiota and CAD and Alzheimer's disease (AD) by MR, and others have explored causal links between blood metabolites and AD by MR (21)(22)(23), but they have not gone further to explore the causal links between the gut microbiota and the blood metabolites in patients with CAD as well as AD, and they have not focused their attention on the disease cluster of CAD combined with cognitive impairment. Therefore, we will conduct a more comprehensive and in-depth exploration by MR to provide new insights into biomarkers and treatments for the disease cluster of CAD combined with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%